High-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder and preparation method thereof

By adding Ge, Zr and other elements to the Sn-Ag-Cu brazing, the alloy composition and preparation process are optimized, and the existing brazing material is insufficient in high-density packaging, and lead-free brazing material with high strength and high elongation is achieved, which is suitable for high-density three-dimensional packaging.

CN119839499APending Publication Date: 2025-04-18HARBIN INST OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510277605.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing Sn-Ag-Cu lead-free solder is difficult to meet the needs of high-strength and high-reliability solder joints in high-density three-dimensional packaging, and there are problems such as pad breakage.

Method used

By adding elements such as Ge, Zr, Al, Fe, In and La to the Sn-Ag-Cu brazing, the alloy composition and preparation process are optimized, the strength and elongation of the brazing material are improved, and the thickness of the intermetallic compound layer at the solder joint interface is reduced.

Benefits of technology

It has achieved high strength and high elongation lead-free solder, significantly improved the reliability of solder joints, and the melting point is lower than that of SAC305, which is suitable for existing electronic packaging processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839499A_ABST
    Figure CN119839499A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder and a preparation method thereof, and belongs to the field of microelectronic packaging. The lead-free brazing filler metal is prepared from, by mass, 0.5%-4% of Ag, 0.1%-1.2% of Cu, 0.05%-1% of Ge, 0.01%-1% of Zr, X is one or more of La, In, Al and Fe, the adding amount of La is 0.001%-0.1%, the adding amount of In is 0.5%-6%, the adding amount of Al and the adding amount of Fe are both 0.001%-0.5%, and the balance Sn. The Sn-Ag-Cu-Bi-Mn-X series lead-free solder disclosed by the invention has the characteristics of high strength and high toughness, and the tensile strength and the elongation of the Sn-Ag-Cu-Bi-Mn-X series lead-free solder are both higher than those of Sn < 3.0 > Ag < 0.5 > Cu solder. The composition proportion of the Sn-Ag-Cu series brazing filler metal with high toughness is finally determined through composition design and auxiliary experiments, and under the synergistic effect of one or more of Ge, Zr, La, In, Al and Fe, the strength and the ductility of the Sn-Ag-Cu series brazing filler metal are both higher than those of SAC305.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of microelectronic packaging, and in particular relates to a high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder and a preparation method thereof. Background Art

[0002] As people's environmental awareness continues to increase, the problem of Pb pollution has received more and more attention. For the protection of the environment and human health, the use of Pb is subject to more and more restrictions. In the field of electronic packaging, traditional SnPb solder is widely used in various electronic components due to its good mechanical properties, wettability, reliability, etc. With the introduction of lead ban laws in various countries, lead-free solder has become an inevitable trend in the development of packaging solder. Sn3Ag0.5Cu (SAC305) lead-free solder with Sn-Ag-Cu eutectic composition is considered to be the best substitute for Sn-Pb solder because of its good mechanical properties.

[0003] However, with the continuous development of electronic information technology, the complexity of electronic systems is increasing, the application scope of electronic products is gradually widening, and the development of electronic products is gradually tending towards multifunctionality, high performance and miniaturization. High-density advanced packaging technology is regarded as the key to breaking through the bottleneck of chip manufacturing technology in the "post-Moore era". In high-density three-dimensional packaging, the size of the package solder joints is getting smaller and smaller, and its reliability is bound to get worse and worse. The mechanical properties of the existing SAC305 are difficult to meet the demand for high-strength and high-reliability solder joints. In order to improve the comprehensive performance of SnAgCu, new high-strength and reliable lead-free solders Innolot and SACQ were developed on the basis of SnAgCu by adding Bi, Sb and Ni. The addition of Bi greatly improves the strength of the solder, and Sb and Ni can improve the thermal fatigue performance of the solder joint. Among them, Ni can also inhibit the growth of the intermetallic compound (IMC) layer of the solder joint. However, the excessive strength of the Innolot solder makes it easy for the pad to break during service. Therefore, it is urgent to develop a lead-free solder with better mechanical properties than SAC305 and high strength and toughness.

[0004] Studies have shown that adding Ge to Sn-Ag-Cu solder can simultaneously improve the strength and elongation of the solder. Although Ge has little effect on the melting point of Sn-Ag-Cu alloy, Ge can reduce the supercooling of Sn-Ag-Cu alloy, promote the nucleation of β-Sn grains, and have the effect of grain refinement. Ge does not react with Sn, and has no solid solubility in Sn at room temperature. It can only precipitate in the form of single particles, providing heterogeneous nucleation sites for the nucleation of Sn, further refining Sn grains. Adding an appropriate amount of Zr to Sn-Ag-Cu can also simultaneously improve its strength and elongation. Zr can also significantly reduce the supercooling of Sn-Ag-Cu alloy and promote the nucleation of β-Sn grains. And at room temperature, Zr has no solid solubility in Sn, and can only form Sn-Zr intermetallic compounds with Sn, which also provides heterogeneous nucleation sites for Sn grains, further refining the grains. An appropriate amount of Zr can inhibit the growth of the interfacial IMC layer. In can reduce the melting point of Sn-Ag-Cu solder, replace Sn atoms in Ag3Sn and Cu6Sn5, form Ag3(Sn, In) and Cu6(Sn, In)5, change the morphology of IMC in solder, and thus improve the strength of solder. Appropriate amount of rare earth elements can inhibit the growth and coarsening of compound phase in Sn-Ag-Cu alloy, and rare earth elements are highly active, which can be enriched on the alloy surface or high energy grain boundary, prevent the growth of individual crystal planes, and play a role in refining the structure. However, excessive rare earth elements will form brown rare earth compounds, which will have an adverse effect on the performance of solder. A small amount of Al can be dissolved into the Sn-Ag-Cu solder matrix, which plays a role in solid solution strengthening. Al can also refine β-Sn grains. Fe can react with Sn to generate a small amount of FeSn2, which can play a role in precipitation strengthening. At the same time, Fe can inhibit the growth of the interface IMC layer and improve the thermal stability of the solder joint. Summary of the invention

[0005] The purpose of the present invention is to meet the demand for high-performance solder for high-density packaging, and to provide a high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder and a preparation method thereof. The present invention is guided by the influence law and mechanism of alloy elements on the structure and performance of Sn-Ag-Cu lead-free solder, selects a variety of alloy elements with fine grain strengthening and precipitation strengthening effects, ensures that the Sn-Ag-Cu solder has high elongation, and greatly improves its tensile strength, and then selects some elements with solid solution strengthening or precipitation strengthening to further improve the strength of the solder, and finally obtains a new type of lead-free solder with high strength and high elongation and a melting point lower than SAC305.

[0006] The present invention improves the mechanical properties of the solder by adding Ge, Zr and one or more elements of Al, Fe, In and La on the basis of the traditional Sn-Ag-Cu solder, and obtains a new lead-free solder with high strength, elongation and a melting point lower than Sn3Ag0.5Cu. Ge can significantly reduce the supercooling of the Sn-Ag-Cu solder, promote the nucleation of β-Sn grains, and have the effect of refining grains. Ge does not react with Sn, nor does it dissolve in Sn. It precipitates in the form of a single substance during the solidification process, provides heterogeneous nucleation sites for the nucleation of β-Sn grains, further refines the grains, and the good fine grain strengthening effect enables Ge to simultaneously improve the strength and elongation of the Sn-Ag-Cu solder. However, the amount of Ge added should not be too high. Too much Ge will precipitate large pieces of Ge single substance in the alloy, which will have an adverse effect on the performance of the solder. Zr can also effectively reduce the supercooling of the Sn-Ag-Cu solder and promote the nucleation of β-Sn grains. Zr reacts with Sn to form Sn-Zr intermetallic compounds, which can provide heterogeneous nucleation sites for the solidification of Sn grains and have the effect of refining grains. Therefore, the good grain refinement strengthening effect of Zr can also improve the strength and elongation of the solder at the same time. An appropriate amount of Zr can also inhibit the growth of the IMC layer of the solder. In can replace Sn atoms in Ag3Sn and Cu6Sn5 to form Ag3(Sn,In) and Cu6(Sn,In)5, change the morphology of IMC in the solder, and then improve the strength of the solder. La can inhibit the growth and coarsening of compound phases in Sn-Ag-Cu alloys, and can also inhibit the growth of some crystal planes. It can also play a role in refining the structure of Sn-Ag-Cu alloys, and has a positive effect on the strength and elongation of the solder. However, too high a rare earth element will form a large block of intermetallic compounds, which will have an adverse effect on the performance of the solder. Therefore, the addition content of rare earth elements generally does not exceed 0.1wt.%. The addition of Al can refine the β-Sn grains and improve the strength of the solder. When the Al content is less than 0.02wt.%, the solder strength can be improved through the solid solution strengthening mechanism. When the Al content is higher, Al-Ag and Al-Cu compounds will be generated in the solder, and both solid solution strengthening and precipitation strengthening mechanisms exist. However, excessive Al content will lead to the precipitation and aggregation of a large amount of Al-Ag and Al-Cu compounds, which will have an adverse effect on the performance of the solder. Fe can react with Sn to generate a small amount of FeSn2, which has the effect of precipitation strengthening. At the same time, Fe can inhibit the growth of the interface IMC layer and improve the thermal stability of the solder joint.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder, wherein the elements and their mass percentages in the lead-free solder are: Ag: 0.5-4%, Cu: 0.1-1.2%, Ge: 0.1-1%, Zr: 0.1-1%, X is one or more of La, In, Al, and Fe, wherein the addition amount of La is 0.001-0.1%, the addition amount of In is 0.5-6%, the addition amounts of Al and Fe are both 0.001-0.5%, and the balance is Sn.

[0009] A method for preparing the above-mentioned high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder, the method comprising:

[0010] Step 1: weigh the metal elements according to the designed alloy composition, first use rosin to evenly apply the surface of each metal element to completely cover the metal raw materials, and then put the raw materials into an induction heating furnace, heat the induction heating furnace to 300°C, keep it warm for 30 minutes, stir it mechanically every 10 minutes during the insulation period, and then add eutectic salt with a mass ratio of LiCl and KCl of 4.5:5.5, heat it to 600-800°C, keep it warm for 60 minutes, and stir it mechanically every 10 minutes during the insulation period; after insulation, cast it into a graphite mold, pass cooling water under the mold to accelerate the cooling rate and prevent the segregation of micro-alloying elements to form large IMC particles;

[0011] Step 2: After applying rosin to the alloy prepared in step 1, place it in an induction furnace and heat it to 300°C until it is completely melted, stir it for 1 minute, cast it into a graphite mold, and cool it in air to obtain a cast alloy structure.

[0012] Furthermore, in step 2, the alloy is stirred immediately after melting and then cast without a heat preservation stage.

[0013] Furthermore, in step 2, the temperature of the high temperature insulation varies according to the types of the added alloy elements.

[0014] The beneficial effects of the present invention compared to the prior art are:

[0015] (1) According to the influence of the added alloying elements on the structure and performance of Sn-Ag-Cu lead-free solder, the elements Ge and Zr with good fine grain strengthening and precipitation strengthening effects are selected to simultaneously improve the strength and elongation of Sn-Ag-Cu lead-free solder or to minimize the decrease in elongation while improving the strength. A small amount of elements that can further improve the strength or reliability are added to improve the overall performance of the solder.

[0016] (2) The melting point is slightly lower than Sn3Ag0.5Cu, which is more suitable for existing electronic packaging processes.

[0017] (3) The Sn-Ag-Cu-Ge-Zr-X series lead-free solder of the present invention has the characteristics of high strength and high elongation. Compared with SAC305, this series of solders achieves both strength and elongation exceeding that of SAC305. The present invention, through component design and auxiliary experiments, finally determines the composition ratio of the Sn-Ag-Cu series solder with high strength and high elongation. Under the synergistic effect of Ge, Zr and one or more of In, La, Al, and Fe, the strength of the Sn-Ag-Cu series solder is significantly improved while maintaining a high elongation.

[0018] (4) The thickness of the IMC layer at the solder joint interface is significantly reduced. Comparative Example 1 and Examples 1 to 4 show that the thickness of the IMC layer at the solder joint interface is significantly reduced under the synergistic effect of multiple elements.

[0019] (5) The preparation method of the solder is simple, the required smelting equipment is simple, and the preparation process can effectively avoid the segregation and growth of the precipitated phase, and avoid the adverse effects of large precipitated particles on the performance of the solder, which is easy to apply to industrial production. Remelting at 300℃ can avoid defects such as component segregation and casting cracks caused by too fast cooling of the alloy liquid during the casting process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The differential scanning calorimetry (DSC) curve of Comparative Example 1 is shown in FIG.

[0021] Figure 2 The differential scanning calorimetry (DSC) curve of Example 1 is shown in FIG.

[0022] Figure 3 The differential scanning calorimetry (DSC) curve of Example 2 is shown in FIG.

[0023] Figure 4 The differential scanning calorimetry (DSC) curve of Example 3 is shown in FIG.

[0024] Figure 5 The differential scanning calorimetry (DSC) curve of Example 4 is shown in FIG.

[0025] Figure 6 This is the microstructure of the reflow soldering interface.

[0026] Figure 7 Schematic diagram of the tensile specimen.

[0027] Figure 8 It is a bar graph of tensile strength and elongation after break of Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0029] Examples 1 to 4 and Comparative Example 1 were prepared with the ingredients shown in Table 1 according to the following preparation method.

[0030] Step 1: Weigh the metal elements according to the designed alloy composition, first use rosin to evenly coat the surface of each metal element so that it completely covers the metal raw materials, and then put it into the induction heating furnace, heat the induction heating furnace to 300℃, keep it warm for 30 minutes, stir it mechanically every 10 minutes during the insulation period, then add the eutectic salt with a mass ratio of LiCl and KCl of 4.5:5.5, heat it to 800℃, keep it warm for 60 minutes, and stir it mechanically every 10 minutes during the insulation period. After keeping warm at 800℃, cast it into a graphite mold, and pass cooling water under the mold to accelerate the cooling rate to prevent the segregation of micro-alloying elements to form large IMC particles.

[0031] Step 2: After applying rosin to the alloy prepared in step 1, place it in an induction furnace and heat it to 300°C until it is completely melted, stir it for 1 minute, cast it into a graphite mold, and cool it in air to obtain a cast alloy structure.

[0032] Furthermore, in step 2, the alloy is stirred immediately after melting and then cast without a heat preservation stage.

[0033] Embodiments 1 to 4 of the present invention are Sn-Ag-Cu-Ge-Zr-X lead-free solders, and the contents of the elements in the embodiments are different. Comparative Example 1 is Sn3Ag0.5Cu, as shown in Table 1.

[0034] Table 1 Ingredients (wt.%) of Examples 1 to 3 and Comparative Example 1

[0035] Ag Cu Ge Zr La Al Fe In Sn Example 1 3 0.5 0.45 0.15 — — 0.005 — margin Example 2 3 0.5 0.15 0.4 0.05 0.005 — — margin Example 3 3 0.5 0.3 0.3 — — — 3 margin Example 4 3 0.5 0.1 0.22 — 0.005 — — margin Comparative Example 1 3 0.5 — — — — — — margin

[0036] It can be seen from Table 2 that the Sn-Ag-Cu-Ge-Zr-X lead-free solder designed by the present invention can significantly improve the strength of the Sn-Ag-Cu solder and reduce the elongation less under the synergistic effect of Ge, Zr and one or more of La, In, Al, and Fe. Some components achieve strength and elongation that exceed SAC305 at the same time. In addition, the melting point of the alloy described in the present invention is lower than Sn3Ag0.5Cu, and the thickness of the IMC layer of the solder joint is also lower than SAC305.

[0037] Table 2 Melting point, tensile strength, elongation after fracture, breaking energy

[0038] Melting point(℃) IMC layer thickness after reflow (μm) Tensile strength(MPa) Elongation after break (%) Example 1 214.96 0.68 59.83 41.96 Example 2 215.41 0.78 53.23 58.53 Example 3 200.51 0.22 56.03 44.31 Example 4 213.70 1.07 54.11 61.24 Comparative Example 1 217.78 2.34 48.61 54.02

[0039] Performance Analysis:

[0040] Figures 1 to 5 The DSC measurement curves of Examples 1 to 4 and Comparative Example 1 are combined with the data in Table 2. It is found from Comparative Example 1 and Examples 1 to 4 that the melting points of the new solders obtained by adding the elements described in the present invention to SAC305 are lower than that of SAC305, and the addition of In causes the melting point of the solder to drop most significantly.

[0041] Figure 6 The microstructure of the reflow soldering interface is shown in Table 2. It can be clearly seen that the thickness of the IMC layer of the Sn-Ag-Cu-Ge-Zr-X lead-free solder of the present invention is lower than that of Sn3Ag0.5Cu. This is because the presence of Zr and Fe elements inhibits the Sn-Cu reaction at the interface, thereby reducing the thickness of the IMC layer.

[0042] Figure 7 This is a schematic diagram of the tensile test specimen of the present invention. Figure 8The bar graphs of tensile strength and elongation after fracture of Examples 1 to 4 and Comparative Example 1, combined with the tensile strength and elongation after fracture data given in Table 2, clearly show that on the basis of Sn3Ag0.5Cu, both Ge and Zr can effectively reduce the supercooling of the Sn-Ag-Cu solder, promote nucleation during the solidification of the liquid solder, and play a role in grain refinement. In addition, the high melting point Ge single substance and Sn-Zr intermetallic compound provide heterogeneous nucleation sites for the solidification of β-Sn, further promote the nucleation of β-Sn, and refine the β-Sn grains. The refinement of the grains leads to the presence of more grain boundaries in the matrix, which can effectively hinder the movement of dislocations and improve the strength of the solder. In addition, a large number of grain boundaries improve the ability of the matrix to accommodate dislocations, thereby improving the elongation of the solder. The precipitated Ge single substance and Sn-Zr intermetallic compound as precipitation phases play a precipitation strengthening effect, which can further improve the strength of the solder. La can inhibit the growth and coarsening of compound phases in Sn-Ag-Cu alloys, and has the effect of refining the Sn-Ag-Cu alloy structure. A small amount of Al has a solid solution strengthening effect in Sn, which can further improve the solder strength. Therefore, under the good fine grain strengthening effect of Ge, Zr and La and the solid solution strengthening effect of Al, the strength and elongation of SAC305 are simultaneously improved. As shown in Comparative Example 1, Example 2 and Example 4, Fe can react with Sn to generate a small amount of FeSn2, which has the effect of precipitation strengthening. At the same time, Fe can inhibit the growth of the interface IMC layer, so the IMC layer of Example 1 is the thinnest. The atomic radius of In is larger than that of Sn. When In replaces Sn atoms in Ag3Sn and Cu6Sn5 or is dissolved in Sn, it can increase the interatomic distance in the system. According to the Lindemann criterion, larger interatomic distances are easier to melt when heated, so the addition of In has the most obvious effect of reducing the melting point of the solder, as shown in Example 3.

[0043] The preparation method of the brazing material is simple, low in cost, has good anti-oxidation effect, is easy to apply to industrial production, and can better avoid the formation of large precipitation phases during the preparation of the brazing material, thereby affecting the performance of the brazing material. Melting again at 300℃ and then casting can avoid defects such as component segregation and casting cracks caused by too fast cooling of the alloy liquid during the casting process.

[0044] The brazing material preparation method of the present invention is simple, the required smelting equipment is simple, the preparation temperature is low, the energy consumption is low, the anti-oxidation effect is good, and it is easy to apply to industrial production. At the same time, it can also avoid the formation of a large precipitation phase during the solidification of the alloy and avoid defects such as component segregation and casting cracks caused by the alloy liquid cooling too fast during the casting process. Using rosin for 300°C insulation and using LiCl and KCl (LiCl:KCl=4.5:5.5, mass ratio) eutectic salt for 800°C insulation can effectively avoid the oxidation of the alloy during the smelting process.

Claims

1. A high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder, characterized in that: The elements and their mass percentages in the lead-free solder are: Ag: 0.5-4%, Cu: 0.1-1.2%, Ge: 0.1-1%, Zr: 0.1-1%, X is one or more of La, In, Al, and Fe, wherein the amount of La added is 0.001-0.1%, the amount of In added is 0.5-6%, the amounts of Al and Fe added are both 0.001-0.5%, and the balance is Sn.

2. A method for preparing the high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder according to claim 1, characterized in that: The method is: Step 1: Weigh the metal elements according to the designed alloy composition, first use rosin to evenly apply the surface of each metal element to completely cover the metal raw materials, and then put the raw materials into an induction heating furnace, heat the induction heating furnace to 300°C, keep it warm for 30 minutes, stir it mechanically every 10 minutes during the insulation period, then add eutectic salt with a mass ratio of LiCl and KCl of 4.5:5.5, heat it to 600-800°C, keep it warm for 60 minutes, stir it mechanically every 10 minutes during the insulation period; after insulation, cast it into a graphite mold, and pass cooling water under the mold; Step 2: After applying rosin to the alloy prepared in step 1, place it in an induction furnace and heat it to 300°C until it is completely melted, stir it for 1 minute, cast it into a graphite mold, and cool it in air to obtain a cast alloy structure.

3. The method for preparing a high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder according to claim 2, characterized in that: In step 2, the alloy is stirred immediately after melting and then cast without a holding stage.

4. The method for preparing a high-strength and high-toughness Sn-Ag-Cu-Ge-Zr-X lead-free solder according to claim 2, characterized in that: In step 2, the temperature of high temperature insulation varies according to the types of added alloy elements.

Citation Information

Patent Citations

  • Sn-Ag-Cu-Ce leadless solder alloy and preparation method thereof

    CN101077553A

  • Serial low-silver and lead-free solder for electronic packaging soft soldering and preparation method thereof

    CN103243234A

  • Corrosion-resistant Sn-Ag-Cu lead-free solder alloy and preparation method thereof

    CN117900689A

  • Lead-free solder material, electronic circuit board and their production method

    JP2005319470A

  • Solder alloy

    JP2013049073A